(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The political and constitutional advances of a state or nation represent possible improvements in the quality of education, the lifestyle of citizens and the guarantee of access to people's rights. The objective of this article is to analyze the political and constitutional advances present in the Constitution of the Republic of Ecuador and in the Organic Law of Intercultural Education in terms of educational inclusion and educational needs that, in the documents indicated, are mentioned as special. The methodology corresponds to a bibliographic review, with a qualitative-descriptive approach. The main results indicate that the analyzed document from Ecuador have advances in their articles and literals related to inclusion in education and educational needs; which represents an advance towards justice and social equality. The study, finally, indicates that updates and teacher training are required, since pedagogical practice can present biases regarding inclusion and attention to diversity, either due to ignorance or omission of the subject.